1988
DOI: 10.1111/j.1365-2915.1988.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of antibody ingested with a mosquito bloodmeal

Abstract: Mouse immunoglobulins were found to persist in Aedes aegypti (L.) mosquito bloodmeals for 2-3 days after ingestion. Immunoenzyme labelling revealed mouse antibody specifically bound to the mosquito midgut epithelium after ingestion; immunogold labelling of thin sections revealed mouse antibody within the cytoplasm of the microvilli on the midgut epithelium. Ingested mouse antibody was not conclusively demonstrated bound to tissues outside the gut, though antibody was detected in mosquito haemolymph using a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Sera from mice bitten by Ae. aegypti localized similarly ( Hatfield 1988b), while sera from rabbits exposed to Ae. communis bites identified a 21.5‐kDa salivary antigen in whole body or SG extracts ( Brummer‐Korvenkontio et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sera from mice bitten by Ae. aegypti localized similarly ( Hatfield 1988b), while sera from rabbits exposed to Ae. communis bites identified a 21.5‐kDa salivary antigen in whole body or SG extracts ( Brummer‐Korvenkontio et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both of these research groups showed that the entry of peroxidase into epithelial cells was achieved directly through the microvilli, not through pinocytotic invaginations, and was accomplished by diffusion and progressive spreading throughout the cells. In addition, IgG passed through midgut epithelial cells (Vaughan and Azad, 1988;Hatfield, 1988) and specifically bound to ovarian tissues (Ramasamy et al, 1988) of the mosquito species by a receptor-mediated mechanism. In our studies, GFP associated with cellular membranes in the gut, hemolymph, and fat body, but was not found intracellularly in the midgut epithelial cells.…”
Section: June 2002mentioning
confidence: 99%
“…Many studies with other insects have shown the uptake of proteins from the diet into the haemolymph (e.g. immunoglobulin G: Hatfield, 1988;horseradish peroxidase: Fishman and Zlotkin, 1984), probably intercellularly through leaky epithelial cell gap junctions (Billingsley and Lehane, 1996). Vaughan et al (1990) calculated that 0.5% of ingested immunoglobulin passed into the haemolymph in mosquitoes.…”
Section: Introductionmentioning
confidence: 99%